The Design Of Self Starting Regulator Using Step-Up Converter Topology For WSN Application - Mohd Nasir, Haslinah; Mohamed Aminuddin, Mai Mariam (World Scientific And Engineering Academy And Society (WSEAS), 2014)

(untitled)
Continuous monitoring is very important for chronic patient, elderly or who was under supervision for recovery from an acute event or surgical. For this Wireless Sensor Network give a solution for continuous health monitoring and able to wirelessly monitoring patient conditions at any time. It is able to generate early warning if received unwanted signal from the patient as well. As known, Wireless Sensor Network is only consumes a little power to turn it on and energy harvesting is able to power up this devices without using the batteries. Continuous monitoring needs a continuous and uninterruptable power source. Hence, energy harvesting is one of the options of the solutions. However, up till now the energy harvesting still develop a low output voltage which is not enough to power on the wireless sensor network . Therefore, this paper proposed a new technique called a self starting DC to DC converter which is able to boost up the input voltage as low as 0.4V to the output voltage of 5.1V. The circuit efficiency is up to 92% which is verified by simulation using LTspice tools. Hardware implementation will be done in future work.